DAMPAK IMPLEMENTASI KEBIJAKAN PENGGUNAAN KARTU TANI TERHADAP EFEKTIVTAS DISTRIBUSI PUPUK BERSUBSIDI DI KABUPATEN SUMBAWA BARAT - RIJAL, MOH SYAMSUL; UMAR, UMAR; ANWAR, ANWAR (GANEC SWARA, 2023)
Subsidized fertilizers played a crucial role in supporting agricultural productivity and food security in Indonesia. However, the distribution of subsidized fertilizers has faced challenges in terms of efficiency and transparency. One of the causes of these issues lies in the problems of a market structure that tends to be oligopolistic and the existence of conspiracies among interests that prioritize personal and group interests, as well as the unavailability of fertilizers at the beginning of the planting season. To address this problem, the Indonesian government introduced the Farmer Card policy as a tool to identify farmers receiving subsidized fertilizers. This research aimed to analyze the impact of the implementation of the Farmer Card on the effectiveness of subsidized fertilizer distribution in West Sumbawa Regency. This study used a quantitative analysis method by collecting data from farmers receiving subsidized fertilizers, fertilizer agents, and stakeholders in West Sumbawa Regency. The data included farmers' understanding of the Farmer Card and its implementation, as well as the subsidized fertilizer redemption process. The research sample was taken using purposive sampling technique with 100 samples from all representative farmers receiving the farmer card in each district. Multiple linear regression analysis was used to measure the relationship between the use of the Farmer Card and the effectiveness of subsidized fertilizer distribution. The research results showed that the implementation of the Farmer Card had a positive impact on the effectiveness of subsidized fertilizer distribution, amounting to 25.70%. Farmers using the Farmer Card tended to receive subsidized fertilizer more efficiently, gain better access to fertilizers, and utilize fertilizers more effectively. Additionally, the redemption of fertilizers through the Farmer Card increased agricultural production and farmers' income.